ENHANCING SMART BUILDING RELIABILITY AND DATA UCONTINUITY USING EDGE COMPUTING (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
Starting from the increase in the number of IoT devices inside buildings, devices that are integrated are the basis of the smart building concept, thus resulting in the exponential growth of the volume of data generated. Such an implementation is feasible but presents certain limitations in terms of the time required for data processing and due to the management of data queues, thus resulting in data losses that can lead to erroneous decisions inside buildings. The article proposes an integration between smart buildings and Edge computing, an integration that aims to demonstrate the benefits of this approach. The system is implemented through the ThingsBoard Edge platform and facilitates access to information generated by several buildings on the campus of the National University of Science and Technology Politehnica Bucharest. To present the benefits of this implementation, a two-month reference period was considered, during which we simulated, in parallel, a smart building infrastructure with and without an integrated edge node. Results confirm superior data continuity for the platform with an integrated edge node; the dependence on an internet connection no longer limits the system's capacity in the absence of a stable connection.
Keywords: Smart building; Edge computing; Internet of Things (IoT)